Produção e composição mineral da beterraba sob doses de sódio e potássio, em solução nutritiva - Carvalho, Karina Fernandes (2008)
High concentrations of sodium can decrease the yield of several crops. However, sodium is a beneficial element to the table beet, it being able to replace the functions of potassium. Studies have showed that sodium is responsible for increased sugar beet and table beet yield. The present work aimed to verify the response of sodium nutrition in replacement and in addition to potassium nutrition on the growth, yield, mineral composition and relationship of sodium to cationic macronutrients in the table beets cv. Early Wonder Tall Top. The experimental was conducted in a greenhouse of the Soil Science Department of the Universidade Federal de Lavras, MG. The plants were put into plastic pots with capacity 3 L, that is, a plant per pot, and the treatments applied which consisted of five proportional replacements of K for Na, respectively, 100 - 0%, 75 - 25%, 50 - 50%, 25 - 75% and 0 - 100% and two additions of sodium in the amount of 25% and 50% of the potassium level recommended for Hoagland solution. It was found that both the replacement and addition of Na to K decreased the leaf area, dry mass of the root, total dry mass, fresh mass of the leaves and fresh mass of table beets root. In addition, also the concentrations of N, P, K, Ca, Mg, Cu, Fe, Mn, Zn and Na of the shoot and N, P, K, Mg, S, B, Cu, Fe, Mn, Zn and Na of the root and the ratios Na:K, Na:Ca and Na:Mg in the beet plants were significant. It was concluded that the replacement of sodium by potassium and the addition of sodium to the satisfactory amounts of potassium contribute to improve both the yield and mineral composition of table beet, using for its own benefit the saline condition of the cultivation place.